Market distortions and local indeterminacy: a general approach - Lloyd-Braga, Teresa (2014)
We provide a methodology to study the role of market distortions on the emergence of indeterminacy and bifurcations. It consists in introducing general specifications for the elasticities of the crucial functions defining the aggregate equilibrium dynamics of the model. This allows us to study how market distortions influence the range of values for the elasticity of input substitution under which local indeterminacy and bifurcations occur, highlighting the main channels and classes of distortions responsible for indeterminacy. Most of the specific market imperfections considered in the related literature are particular cases of our framework. Comparing them we obtain several equivalence results in terms of local dynamic properties. Applying this methodology to the Woodford [30] framework we find that distortions in the capital market, per se, do not play a major role. We further show that, for empirically plausible values of elasticity of substitution between inputs, indeterminacy requires a minimal degree of distortions. This degree seems to be high under output market distortions, while with labor market distortions the required degree is empirically plausible.